HUBUNGAN BEBERAPA FAKTOR DENGAN FUNGSI PARU PADA PEKERJA WANITA DI INDUSTRI FURNITURE PT. EBAKO NUSANTARA SEMARANG TRIMESTER II TAHUN 2017 - Cristin Oktaviani Goslesia Yunita Alfabet; Suhartono Suhartono; R. Djoko Nugroho (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Dust is one of the polluted substances which is found in furniture industry which can be caused an occupational disease. Respiratory diseases are an occupational disease in an industry that was often found in developing countries, one of which related was lung function. Based on data of ILO (2013), 30% - 50% workers in developing countries was suffered from lung function disorder that is pneumoconiosis.The purpose of this study was to analyzed the correlation of several factors with lung function on women workers in furniture industry Ebako Nusantara Semarang Factory. The method was used explanatory research using cross sectional study. The populations in this research were most of women workerswho did sandingactivities in the final sanding and finishing department as much as 76 workers then 37 workers were used as sample with purposive sampling technique. Data was analyzed by univariat and bivariat using Continuity correction dan Fisher’s exact test. The result of univariat analyze showed that the largest percentage of workers are with >5 years of work period (56,8%), nutrition status (62,2%), didn’t used PPE (59,5%) and lung function with suffered diagnosis (67,6%). Bivariat analyze showed that there’s no correlation between work period (p value=1,000) and nutrition status (p value=0,306) with lung function while the used of PPE has a correlation with lung function (p value = 0,036, CI = 0,986-3,118). It was suggested to workers for always use mask and to do MCU on workers by human capital head.